(untitled) (Research, Society and Development, 2024)
Introduction: Sepsis is an organic dysfunction caused by a response to an infection, one of the most affected organs is the kidney, causing acute kidney injury (AKI). The aim of this study is to relate the most recent evidence of understanding the pathophysiology and use of biomarkers of sepsis related to acute kidney injury. Methodology: This research is a narrative review of the literature, which sought to address acute kidney injury in sepsis. The research used the Scielo, PubMed MEDLINE and LILACS databases, with the keywords “sepsis” and “acute kidney injury”. Results and Discussion: A discussion stands out indicating that sepsis-induced AKI takes into account criteria such as sepsis from the Surviving Sepsis Campaign and those of AKI from KDIGO. Biomarkers are important when there is AKI related to sepsis. Its diagnosis is made through tools such as SOFA, SIRS and NEWS, but qSOFA is no longer used in this identification. Treatment is with broad-spectrum antibiotics, with caution in the use of nephrotoxic agents, and norepinephrine as a first-line vasopressor. Conclusion: It is understood, therefore, that through this study it was possible to understand more about the pathophysiology of sepsis related to acute kidney injury, with inflammation being prevalent as an essential factor for AKI. Furthermore, there is still a prevalence of people who require hemodialysis or renal replacement after sepsis with acute kidney injury, making evident the need for study and training of professionals in the area.